SOCIAL DIMENSION OF INNOVATION RESEARCH IN THE CONDITIONS OF SOCIAL TRANSFORMATIONS - Тетяна ЄРЕСКОВА; Олег МАЗУРИК (Cхід)
The article is devoted to understanding the social dimension of perception of innovations, which allows to determine the vector of perception of transformational changes in society. The urgency of the problem is due to the multicomponent processes of social transformations and the polyvariety of their consequences for social development. The theoretical foundations of scientific research are based on the analysis of theories of social transformations, stages of the “innovation life cycle”, typology of subjects of perception of innovations existing in the socio-humanitarian discourse. The article substantiates the expediency of taking into account the methodological aspects of the study of innovation as a social process through the emphasis on the impact of social well-being of members of society on the perception of innovative changes as a result of socio-economic, political, cultural transformations. A classification of innovations is proposed, depending on their perception by members of society (“recognized innovations”, “fragmentary innovations”, “marginal innovations”, “antagonistic innovations”, “rejected innovations”). The possibilities of their empirical classification were tested based on the results of the secondary analysis of the data of the annual monitoring “Ukrainian Society: Monitoring Social Changes” (Institute of Sociology of the National Academy of Sciences of Ukraine). As a result of the research it was possible to determine the basic indicators of perception of social reality by members of Ukrainian society in periods of social transformations (“satisfaction with one’s position in the period of social transformations”, “ability to live in new social conditions”, “satisfaction with one’s own life”); to trace their dynamics in the periods defined in the article by the authors as stages of social transformations (1994, 2004, 2014, 2020). According to the authors, it is during these periods that certain socio-cultural changes, which determine the vital activity of Ukrainian society, have been initiated. It is concluded that indicators of social well-being of members of society should be analyzed and taken into account when planning innovations, because it allows to predict and consider potential social reactions not only to the emergence of innovations introduced as part of social transformation, but also their level of social support in conditions of social transformations.